SERTULUM DIPTEROCARPACEARUM MALAYENSIUM-âV* - SLOOTEN, D. F. VAN (Research Center for Biology, 1952)
Some 70 years ago Thiselton Dyer showed Dipterocarpaceae from New Guinea to the Linnean Society of London. This event is referred to in the